Measuring the impact of COVID-19 on climate smart agriculture strategies of smallholder farmers in coastal Bangladesh - Amjath Babu, Tharayil Shereef; Mamun-ur-Rashid; Sumona Shahrin; Krupnik, Timothy J. (Elsevier, 2025)
Context: Climate-smart agriculture (CSA) strategies of smallholder farmers include intensification, diversification, alteration of farming practices, and transformation to other enterprises, along with mitigation of greenhouse gases and temporary or permanent migration. The determination of CSA strategies relies on livelihood capitals, namely physical, natural, human, social, financial, information, and technological capitals of smallholder farmers. The COVID-19 pandemic has prompted shifts in CSA strategies, with variations dependent on these capitals. Objective: The study aims at developing a conceptual and methodological framework to understand external disruptions like the impact of COVID-19 on CSA adoption and how the livelihood capitals and environmental conditions influence these impacts. Methods: The study develops a composite indicator of the changes in CSA strategies and links them to indicators of human, physical, financial, social, natural, and information capital through quantitative regression models. Results and conclusion: The results unraveled varied impacts of the COVID-19 pandemic on climate-smart agriculture in Bangladesh. The findings revealed that among the climate-smart agricultural strategies, intensification efforts were least affected, diversification showed a mixed picture, whereas seasonal migration experienced a significant negative impact. Ownership of physical capital, such as machinery, enhanced intensification, given the shortage of hired machinery and labor services during the pandemic period. Similarly, information capital, as reflected in mobile phone ownership, played a decisive role in improving farm productivity and income. Level of income loss during COVID period and difficulties in accessing credit increased migration while size of loan increased diversification. Canal irrigation access increased intensification and migration and reduced diversification. Significance: In response to the COVID-19 crisis, the government of Bangladesh has supported activities that favored the intensification of production of major crops. It appears to be successful in maintaining the intensity of staple crop cultivation despite the substantial impacts of COVID-19. It is observed that the rate of change in uptake of resilience-building agricultural practices, greenhouse gas mitigation practices and transformation to aquaculture from agriculture were stalled during the COVID-19 pandemic years. The results argue for policies to improve how finance is provided, extension services are delivered, and cellular mobile access is ensured, especially for marginal and women farmers. Difficulties in accessing loans increased migration and larger sized loans pushed farmers to diversification. Therefore, schemes to restructure farm credit need to be explored. To enhance migration as an adaptation strategy during pandemic time, it is necessary to impart additional skills and provide support schemes to offset income loss.